ACTIVITY PACKAGE TO CREATE VALUE APPRECIATION OF COMMUNITY ART FOR YOUTH: CASE STUDY OF LAMPANG GOLD LEAF LACQUER DECORATIONS - Srijai, Nattapol; Pholprasert, Apichart (Journal of Social Science and Cultural, 2023)
This research aimed to explore the fundamental principles behind the design of an activity set aimed at promoting the appreciation of community arts among the youth: A Case Study of Lampang Gold Leaf Lacquer. This research is Research and Development by employing Bloom (et al.) taxonomies of learning objectives, focusing on the Cognitive Domain and Psychomotor Domain, along with the Theory of Arts Education emphasizing Thai wisdom, Principles of Organizing Community Art Activities, and insights from expert Interviews. This sample group consists: 1) Community artists, 2) Experts in Thai Art, 3) Experts in Art History, 4) Teachers, 5) Community art activity organizers, totaling 15 participants by using data collection tools as data collection through interviews to gather historical background and the relationship between artwork and the community. The data was then analyzed using content analysis. The findings from the document study and expert interviews could be summarized as research results in a series of activity sets aimed at promoting the appreciation of community arts among youth. The activity set comprised 5 aspects, including 1) Content, 2) Technical, 3) Activity formats, 4) Participation, 5) Dissemination. The activity set was divided into 4 activities, including 1) Community Learning , Exploring Local Artistic Works, 2) 4 Techniques : Lai Kham Artwork 3) Collaborative Creativity Activity: Creating Contemporary. 4) Local Art in Lampang Exhibition. The data collection tools for evaluating the usage of the activity set consists 1) Test questionnaire to assess participants' understanding of the knowledge related to Lampang Craftsmenship artwork "Lai Kham". 2) Measurement form of participants' attitudes toward the significance. 3) Measurement form to measure individual perceptions of the value derived from observing an individual's behavior. 4)Assessment form to determine satisfaction levels regarding the format of the activity set. The evaluation IOC from qualified found that such a set of activities had a consistency of 0.8 levels.